2019
DOI: 10.1002/acn3.50827
|View full text |Cite
|
Sign up to set email alerts
|

Key inflammatory pathway activations in the MCI stage of Alzheimer’s disease

Abstract: Objective To determine the key inflammatory pathways that are activated in the peripheral and CNS compartments at the mild cognitive impairment (MCI) stage of Alzheimer’s disease (AD). Methods A cross‐sectional study of patients with clinical and biomarker characteristics consistent with MCI‐AD in a discovery cohort, with replication in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) cohort. Inflammatory analytes were measured in the CSF and plasma with the same validated multiplex analyte platform in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 48 publications
(58 reference statements)
6
26
1
Order By: Relevance
“…MCI patients with higher levels of CCL2 at baseline also exhibit faster rates of cognitive decline and shorter time-to-conversion to AD, suggesting that CCL2 signaling may be most relevant during early disease stages (64,65). Similarly, increasing levels of CCL2 in patients with MCI and AD are associated with elevated levels of total-tau and phospho-tau in CSF, smaller medial temporal lobe volume, and lower cognitive memory scores (66)(67)(68). In the present study, IHC detection of CCL2 revealed that, in the absence of extracellular plaques and pathological tau, Aβ-burdened neurons represent the predominant source of CCL2 within the human medial temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…MCI patients with higher levels of CCL2 at baseline also exhibit faster rates of cognitive decline and shorter time-to-conversion to AD, suggesting that CCL2 signaling may be most relevant during early disease stages (64,65). Similarly, increasing levels of CCL2 in patients with MCI and AD are associated with elevated levels of total-tau and phospho-tau in CSF, smaller medial temporal lobe volume, and lower cognitive memory scores (66)(67)(68). In the present study, IHC detection of CCL2 revealed that, in the absence of extracellular plaques and pathological tau, Aβ-burdened neurons represent the predominant source of CCL2 within the human medial temporal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, expression of the brain-type ryanodine receptor, RYR3, in thymomas has been shown to be associated with TAMG (8), but in this case we now find that the association is strongest in type B2 thymomas (Figure S2). Of note, pathways that play a role in the above mentioned neurodegenerative diseases, have been found enriched in a variety of immunobiological settings, including chronic infections, graft-vs.-host disease, cancer biology, cell death, and inflammation (15)(16)(17). Likewise, the "Adherens junction" pathway that was the most significantly downregulated TAMG-associated pathway in type AB thymomas ( Table 1) has been linked to thymic hypoplasia and lymphopenia (18) and to various autoimmune diseases in conjunction with the leakiness of several blood-tissue and inter-epithelial barriers (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight MCI-AD patients at baseline in whom the diagnosis of MCI-AD with CSF Ab 42 and p-tau 181 levels consistent with a diagnosis of AD and consensus evaluation of two neurologists and a neuropsychologist the details of which have been published previously. 17,18 The study was approved by the Cleveland Clinic Institutional Review Board. Eight patients did not complete the longitudinal evaluations due to nonmedical reasons by their personal choice.…”
Section: Discovery Cohortmentioning
confidence: 99%
“…The biomarker analysis protocol used in this study has been previously described (18). In brief, CSF and plasma were collected and analyzed by an independent laboratory via the validated RBM Multi-Analyte Profile (MAP) platform from Myriad Genetics (Salt Lake City, UT).…”
Section: Inflammatory Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation